2014
DOI: 10.5812/numonthly.15991
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Varicocelectomy on the Patients With Premature Ejaculation

Abstract: Background:Premature ejaculation is one of the most problems in clinical practice. The association between varicocele and premature ejaculation was poorly understood. The effects of varicocelectomy on premature ejaculation in varicocele patient was studied.Objectives:The aim of this study was to determine the impacts of varicocelectomy on patients with both premature ejaculation and varicoceles.Patients and Methods:This was a clinical trial study, conducted on 124 patients (20-35 years old), with varicoceles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The authors also note that venous congestion through a connection between the testicular and prostatic venous systems may predispose a varicocele patient to prostatitis. Consistent with these findings, there have been preliminary reports from methodologically flawed studies of improvements in men with PE treated with varicoelectomy ( 138 , 139 ).…”
Section: Varicocele and Pementioning
confidence: 53%
“…The authors also note that venous congestion through a connection between the testicular and prostatic venous systems may predispose a varicocele patient to prostatitis. Consistent with these findings, there have been preliminary reports from methodologically flawed studies of improvements in men with PE treated with varicoelectomy ( 138 , 139 ).…”
Section: Varicocele and Pementioning
confidence: 53%
“…One study reported an association between varicocele and premature ejaculation, likely owing to varicocele-related congestion of the periprostatic venous plexus and prostate inflammation 158 . Varicocelectomy has been associated with improvement in premature ejaculation 159,160 . However, further prospective studies with larger patient groups are needed to confirm this finding 161 .…”
Section: Hivmentioning
confidence: 99%
“…No sperm counts were reported. The effect of varicocele treatment on PE have been investigated in other two studies 70 , 71 ; however, both of them were conducted on patients with semen impairment but no evidence of couple infertility and for this reason they will not be taken in account in our analysis.…”
Section: Remarksmentioning
confidence: 99%